Food Quality, Safety and Technology - Lima, Giuseppina P. P.; Vianello, Fabio; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2013)
The present book collects selected contributions from researchers working in the field of food science, and participating at the second spring school for Food Quality, Safety and Technology, which was held in Botucatu (São Paulo, Brazil), from September 24th to 27th, 2012, at the Botucatu Campus of the Universidade Estadual Paulista Julio Mesquita Filho (UNESP). The goal of the conference was to provide a scientific forum covering large areas of agronomy, nutrition, food science and technology, veterinary and other areas related to food technology development. Teachers, professionals, graduate and post-graduate students in Food Science; Food and Agriculture Engineering; Veterinary, Science and Food Technology and related areas were addressed by providing an exchange of knowledge and technologies. The initiative aimed to establish uniform, globally recognized scientific principles on food safety and quality, which could be consistently applied to industry and production sectors and stakeholders, taking into account that effective food control systems are essential to protecting the health and safety of domestic consumers, to guaranteeing the safety and quality of foods entering international trade, and to ensuring that imported foods conform to national requirements
Antioxidants in Brazilian plant species -- Quality and potential healthy traits in vegetables and berries -- Unit processing operations used in minimally processed horticultural products: quality and safety preservation -- Analytical aspects for tropical meat quality assessment -- Lycopene bio-availability and effects on health -- The Post-Harvest of Tropical Fruits in Brazil -- Impact of animal feeding on the nutritional value and safety of food of animal origin -- Surveillance of anabolic abuse in cattle: suitability of transcriptomic technologies as screening tools -- The dairy products, nutritional and legal value, an opportunity for the defense and promotion of the territory -- Production of bioactive compounds by microorganisms using solid phase fermentation -- Biosensors for food quality and safety -- Natural Ingredients as Additive for Active Antioxidant Food Packaging.
Keywords: Chemistry; Food science; Nutrition; Biochemistry; Chemistry; Food Science; Biochemistry, general; Nutrition